Recombinant human tissue factor pathway inhibitor exerts anticoagulant, anti‐inflammatory and antimicrobial effects in murine pneumococcal pneumonia - VAN DEN BOOGAARD, F. E.; BRANDS, X.; SCHULTZ, M. J.; LEVI, M.; ROELOFS, J. J. T. H.; VAN 'T VEER, C.; VAN DER POLL, T. (Journal of thrombosis and haemostasis, 2011)
See also Maroney SA, Mast AE. Tissue factor pathway inhibitor and bacterial infection. This issue, pp 119–21. Summary.  Background: Streptococcus (S.) pneumoniae is the most common causative pathogen in community‐acquired pneumonia and a major cause of sepsis. Recombinant human tissue factor pathway inhibitor (rh‐TFPI) attenuates sepsis‐induced coagulation and has been evaluated in clinical trials involving patients with sepsis and community‐acquired pneumonia. Objective: To examine the effect of rh‐TFPI on coagulation, inflammation and bacterial outgrowth in S. pneumoniae pneumonia in mice, with or without concurrent antibiotic treatment. Methods: Pneumonia was induced by intranasal inoculation with S. pneumoniae. Mice were treated with placebo, rh‐TFPI, ceftriaxone or rh‐TFPI combined with ceftriaxone. Early (8 h) and late (24 h) initiated treatments were evaluated. Samples were obtained 24 or 48 h after infection, for early and late initiated treatment, respectively. In vitro, placebo or rh‐TFPI was added to a suspension of S. pneumoniae. Results: Rh‐TFPI reduced pneumonia‐induced coagulation; rh‐TFPI with ceftriaxone further attenuated coagulation relative to ceftriaxone alone. Rh‐TFPI inhibited accumulation of neutrophils in lung tissue and reduced the levels of several cytokines and chemokines in lungs and plasma in mice not treated with antibiotics; in these animals, rh‐TFPI initiated 24 h after infection decreased pulmonary bacterial loads. In vitro, rh‐TFPI also inhibited growth of S. pneumoniae. Conclusions: Therapeutic rh‐TFPI attenuates coagulation, inflammation and bacterial growth during pneumococcal pneumonia, whereby the latter two effects only become apparent in the absence of concurrent antibiotic treatment.